Grammatical Profiling of College Students: Basis for Educational Intervention - Capoy, Bee Jess W.; Capoy, Bee Jess W.; Enclona, Janice P.; Florentino, Colleen Kay C. (Digos City UMDC, 2019)
This study aimed to determine the demographic profile of the respondent in terms of specialization, determine the lev el of grammatical proficiency of students in terms of parts of speech, classification of verbs, and sentence structures, to identify the overall performance on grammatical proficiency test as analyzed by specialization, and to formulate an education intervention plan. The study used the descriptive method of research wherein the quantitative data were gathered using a grammar proficiency test questionnaire. The respondents were 179 freshmen students of the Department of Teacher Education in UMDC. After a thorough analysis, results showed that the level of grammar proficiency of the respondents in terms of parts of speech, classification of verbs, and sentence structures is beginning which means that the respondents described to have very poor level on grammatical achievement. Moreover, the overall performance on grammatical proficiency test as analyzed by specialization showed that BSED-Biological Science got the highest scoring area of 53%, followed by BSED -English rated 51%, next was BSED-Mathematics rated 50%, and then followed by BSED- Filipino and BPE who got the same average score of 42% respectively. Based from the findings of the study, the researchers crafted an educational intervention plan to address the deplorable performance of the respondents.
Keywords: Education -- English -- Undergraduate Thesis